DeFi, Blockchain and Cryptocurrencies: Proposing a Global Money Matrix for the Blockchain Era - Tayazime, Jihane; Moutahaddib, Aziz (European Scientific Journal, ESJ, 2023)
Unlike early civilizations with an entire economy built around agriculture and the practicality of the barter system, today’s complex economies require immediate, low-cost transactions. The digitalization of transactions is helping economies develop through various new assets and currencies. The appearance of DeFi, CBDC’s, and many blockchain based systems has created a bit of a debate among researchers. Consequently, the matter maintains a certain ambiguity, which requires more research. In this paper, we will be discussing how blockchain is revolutionizing the financial sector, by creating decentralized finance and central banks’ digital currencies. We will then propose a new global money matrix starting with a short literature review of existing definitions and categorizations since there still is a lack of understanding and standardization of currency categories, especially digital currencies. Then we will do the same for CBDC by categorizing it by component: participants, categories, and application scenarios.